VD_FINDINFO Jug / 2022 / 385 vom 23. Mai 2022 - VD Tribunal cantonal (2022)
DÉLIT MANQUÉ, MEURTRE, MEURTRE PASSIONNEL, CONTRAINTEDROIT PÉNAL, EXPULSIONDROIT PÉNAL | 113 CP, 22 ad 111 CP, 22 ad 181 CP, 41 CP, 66a CP